Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s11130-011-0250-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Phenolic Antioxidant-mediated α-glucosidase Inhibition of Ascophyllum nodosum

Abstract: Ascophyllum nodosum is a brown seaweed that grows abundantly in the US Northeast coastal region. This study examined the seasonal variation of A. nodosum in phenolic contents and subsequent antioxidant, α-glucosidase and α-amylase inhibitory activities. A. nodosum was harvested monthly and extracted in hot water and the resulting extracts were spray-dried. The results indicate a clear seasonal variation in terms of phenolic content, with June and July being the highest (36.4 and 37 mg/g, respectively) and May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 25 publications
4
30
1
Order By: Relevance
“…1, Table 2) correlate with observed phenolic contents ( Table 1) (PCC r = 0.973). This is in agreement with previous reports suggesting that phenolic phytochemicals have carbohydrate hydrolyzing enzyme inhibitory activity [5,9,10]. Also, our findings suggest that to ensure the highest rat α-glucosidase inihibitory activity it is important to identify the appropriate point that the lignification process is initiated.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…1, Table 2) correlate with observed phenolic contents ( Table 1) (PCC r = 0.973). This is in agreement with previous reports suggesting that phenolic phytochemicals have carbohydrate hydrolyzing enzyme inhibitory activity [5,9,10]. Also, our findings suggest that to ensure the highest rat α-glucosidase inihibitory activity it is important to identify the appropriate point that the lignification process is initiated.…”
Section: Resultssupporting
confidence: 93%
“…Recent studies showed that phenolic phytochemicals from botanical sources are natural inhibitors of α-amylase and α-glucosidase and thus can be used to manage postprandial hyperglycemia with minimal side effects [5,9,10]. More specifically, plants belonging in the Lamiaceae family as well as corn, bean, and pumpkin extracts have shown a good inhibitory profile against carbohydrate degrading enzyme such as α-glucosidase [5,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, inhibition of these enzymes can significantly decrease the postprandial hyperglycemia after a mixed carbohydrate diet and can be a key strategy in the control of diabetes mellitus (5). Recent research findings have shown that plant-derived phenolics play a role in mediating α-glucosidase and α-amylase inhibition and thus have potential to contribute to the management of type-2 diabetes (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Asparagopsis armata cultured in fishpond effluents at higher nitrogen fluxes had an increased content of mycosporinelike amino acids (MAAs) which have a UV-protective and antioxidant function [9], and the reducing capacity of extracts from the red macroalga Palmaria palmata (dulse) harvested from a high UV-exposure environment was 86% higher than extracts from dulse harvested from a low UV-exposure environment [8]. In addition, there is substantial data on how the antioxidant content of marine macroalgae in natural habitats is influenced by abiotic stresses such as light, temperature, and desiccation stress [10,11]. On-land culture manipulations therefore provide the potential to exploit or enhance the antioxidant capacity of the biomass.…”
Section: Introductionmentioning
confidence: 99%